2021
DOI: 10.1002/hipo.23382
|View full text |Cite
|
Sign up to set email alerts
|

The structure of hippocampal circuitry relates to rapid category learning in humans

Abstract: Prior work suggests that complementary white matter pathways within the hippocampus (HPC) differentially support the learning of specific versus general information. In particular, while the trisynaptic pathway (TSP) rapidly forms memories for specific experiences, the monosynaptic pathway (MSP) slowly learns generalities.However, despite the theorized significance of such circuitry, characterizing how information flows within the HPC to support learning in humans remains a challenge.We leveraged diffusion-wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Indeed, several studies have found that activation in the anterior hippocampus is related to category learning (Mack et al, 2016(Mack et al, , 2018Zeithamova et al, 2008) and to prototypestyle learning specifically (Bowman & Zeithamova, 2018). Further, activation in the hippocampal body and tail is associated with learning categories that involve exceptions (Davis, Love, & Preston, 2012), which is also consistent with the finding that TSP white matter integrity predicts exception learning (Schlichting et al, 2021). Thus, neuroimaging evidence suggests a strong involvement of the hippocampus in category learning, with some evidence consistent with our account of the nature of this involvement.…”
Section: Neuroimaging Evidence Of Hippocampal Involvement In Category...supporting
confidence: 79%
See 3 more Smart Citations
“…Indeed, several studies have found that activation in the anterior hippocampus is related to category learning (Mack et al, 2016(Mack et al, , 2018Zeithamova et al, 2008) and to prototypestyle learning specifically (Bowman & Zeithamova, 2018). Further, activation in the hippocampal body and tail is associated with learning categories that involve exceptions (Davis, Love, & Preston, 2012), which is also consistent with the finding that TSP white matter integrity predicts exception learning (Schlichting et al, 2021). Thus, neuroimaging evidence suggests a strong involvement of the hippocampus in category learning, with some evidence consistent with our account of the nature of this involvement.…”
Section: Neuroimaging Evidence Of Hippocampal Involvement In Category...supporting
confidence: 79%
“…Lesioning the TSP resulted in poor recognition with preserved categorization ability. Consistent with these behaviors, a recent study found that strong TSP white matter integrity predicts the ability to learn category exceptions (Schlichting, Gumus, Zhu, & Mack, 2021). We thus propose that the properties of the TSP should make it useful beyond its traditional domain of episodic memoryit should contribute to any new learning that requires memory for arbitrary, as opposed to systematic, information.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The trisynaptic circuit of the hippocampus is organized transversely along the hippocampus. Association and commissural fibers are organized along the anteroposterior axis [63].…”
Section: Cortico-limbocortical Neuronal Networkmentioning
confidence: 99%